Investigating the effect of melanopsin gene therapy in the degenerate retina - De Silva, S (2015)
Retinal degenerations such as retinitis pigmentosa affect 1 in 3000 people causing visual loss and blindness. In these conditions, photoreceptors are lost whereas other retinal cells and central visual pathways remain largely intact. A strategy for restoring vision in patients with end-stage disease would be to introduce a light sensitive protein into remaining inner retinal cells to make them directly light sensitive. The aim of this thesis was to assess whether the human photopigment melanopsin, normally present in intrinsically photosensitive ganglion cells, could be delivered to other residual cells of the degenerate retina using an adeno-associated viral (AAV) vector, and whether this could restore visual function. Several AAV serotypes were tested in the rd1 mouse model of end-stage retinal degeneration. The most effective was found to have a single tyrosine to phenylalanine mutation in the AAV capsid (rAAV2/8 Y733F), and this vector was also able to transduce bipolar cells in human retinal samples cultured ex-vivo. Further evaluation of the vector was then performed to identify whether delivery using a ubiquitous or bipolar cell specific promoter gave optimal expression, and that comparing a wild type to a codon optimised sequence was also assessed. Longevity of expression was also assessed with robust levels of melanopsin seen in the degenerate retina fifteen months after a single subretinal injection. Retina transduced using the optimised vector was tested for functional light responses using ex-vivo multi-electrode array recordings and in vivo light pulsing, with results from both highly indicative of functional photosensitivity mediated by expressed melanopsin. Furthermore, laser speckle cortical imaging demonstrated a light-dependent change in blood flow in the visual cortex of treated mice. Finally to assess whether visual function was restored, in vivo testing of the pupil light response revealed augmented pupil constriction compared to controls two months after subretinal injection of the vector. This effect was maintained and even greater at thirteen months. Further behavioural testing demonstrated that following vector administration both two and thirteen months previously, mice were able to detect a change in visual environment, whereas control rd1 mice were not. These data indicate that the increased photosensitivity derived from expression of human melanopsin in the degenerate retina can generate functionally useful information, which can restore light-driven responses and even enhance performance in a test that relies on image–forming vision in mice with end-stage retinal degeneration. Therefore with further development, this optogenetic strategy has great potential for the treatment of patients with end-stage retinal degeneration.